A review of passenger ride comfort in railway: assessment and improvement method. Issue 2 (11th June 2022) - Peng, Yong; Zhou, Jiahao; Fan, Chaojie; Wu, Zhifa; Zhou, Wenjun; Sun, Dayan; Lin, Yating; Xu, Diya; Xu, Qian
Abstract: Passenger ride comfort has become a focus of attention in rail transportation equipment design, manufacture and later operation to meet people's demand for travel quality. However, comfort is a very subjective concept, which is difficult to quantify and evaluate directly, and can be affected by various factors, leading to the corresponding technologies for ride comfort improvement becoming diverse. In this paper, recent research on the assessment method and improvement measures of railway passenger ride comfort is reviewed. The main types of ride comfort are summarized first according to the sources of discomfort, including static comfort, vibration comfort, noise comfort, aural pressure comfort, thermal comfort and visual comfort. The current assessment methods of ride comfort are introduced from the aspects of environmental parameters and human parameters based on the nature of evaluation indicators. Finally, the improvement technologies for each type of ride comfort are presented.